Effectiveness of Bottle Size Variation on the Growth of Dendrobium Striaenopsis Orchid Plantlets - Andriani, Diska Rahma Putri; Rahayu, Praptining; Prasetiyo, Prasetiyo (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
The production of Dendrobium striaenopsis orchid cultivation in Indonesia has many obstacles including limited seed provision, low seed quality and cultivation techniques that have not been done well, while orchid enthusiasts always increase every year. Propagation of orchid plants by conventional means requires a long time to obtain a large number of plant saplings, therefore alternative cultivation using tissue culture techniques is needed. In vitro tissue culture techniques are widely used as a fast and efficient way to produce D. striaenopsis orchid plants, but not infrequently there are factors that affect the production of orchids, one of which is bottle size.  The purpose of this study is to determine the effect of the effectiveness of bottle size variations on the growth of        D. striaenopsis plantlets after comparing the difference in bottle volume and knowing the optimum size of bottles used for D. striaenopsis plantlet growth. The study was conducted from May to August 2023 in the Laboratory CV. Candi Orchid, Semarang City. The method used was the observation and experimental method after which it was continued with the One Way Anova test and further test T. In this study using Vacin and Went medium with a size of 60 ml by providing treatment variations in bottle sizes of 250 ml, 500 ml and 750 ml with 4 repeats. The result of this study is that a 750 ml bottle used in the tissue culture technique of D. striaenopsis Orchid is effective in use even though the growth of plantlets does not occur a significant difference, this is due to environmental factors, namely light intensity and duration of irradiation